2021
DOI: 10.1039/d1ra05340j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal and mechanical properties of silicone rubber with γ-ray irradiation-induced polysilane-modified graphene oxide/carbon nanotube hybrid fillers

Abstract: In this work, functionalized silicon rubber with hybrid nanocarbon filler was prepared. The composites with good resistance ability to stress relaxation can be used as underfill to improve the thermo-mechanical reliability of flip-chips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…With the participation of air and water vapor, the pigments change into colorless or light-colored compounds, resulting in the macroscopic fading of the prosthesis [ 6 ]. After testing the color stability of five pigments in a silicone rubber, Cao et al and others concluded that the early color change of the prosthesis may be caused by the fading of pigments sensitive to ultraviolet light, while the color change after the long-term use may be caused by the color change in the silicone rubber [ 7 ]. Zhang et al and others tested the influence of three common exogenous colorants (tea, coffee, and red wine) on the dyeing of SY-1 silicone rubber.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the participation of air and water vapor, the pigments change into colorless or light-colored compounds, resulting in the macroscopic fading of the prosthesis [ 6 ]. After testing the color stability of five pigments in a silicone rubber, Cao et al and others concluded that the early color change of the prosthesis may be caused by the fading of pigments sensitive to ultraviolet light, while the color change after the long-term use may be caused by the color change in the silicone rubber [ 7 ]. Zhang et al and others tested the influence of three common exogenous colorants (tea, coffee, and red wine) on the dyeing of SY-1 silicone rubber.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is interesting to mention that graphene can be modified by other kinds of methods such as gamma irradiation, 96–99 electrochemical methods, 44,100,101 and heat treatment. 61,102–104…”
Section: Graphenementioning
confidence: 99%
“…Therefore, the crosslinking density, thermal conductivity, tensile strength, and elongation increase gradually when 0.1 wt% to 3 wt% of GO/CNTs-silica is present in silicone rubber. 96…”
Section: Graphenementioning
confidence: 99%
See 2 more Smart Citations